Pengaruh Pengunaan Alat Kontrasepsi dengan Kejadian Kematian Neonatal Dini : Effects of Contraceptive Use with the Incidence of Premature Neonatal Death - Mona Safitri Fatiah (Poltekkes Kemenkes Palu, 2022)
Introduction: Early Neonatal Death gave of 2/3 infact death. The purpose this study aim to the effect of family planning with early neonatal death. Methode: This study is a quantitative study with the design of case kontrol research at primary health care in Sarmi on June 1st - November 31st, 2020 with case samples are mothers who experienced early neonatal death of 34 people and kontrol samples are mothers who did not experience early neonatal events of 166 people with a ratio of 1: 5. This study uses medical record data in 2017-2019 Puskesmas Sarmi with logistic regression analysis of risk faktor models processed using STATA 14. Results: The results of this study indicate that there is an effect of using contraceptives on early neonatal mortality after being controlled by confounding variables such as gestational age, gestational age, LILA, Hb levels, and ethnicity (p value 0.0001 with an OR value of 11.4 (95%CI= 4.5 – 29.5). Optimization of care mentoring roles in efforts to increase PUS and WUS participation in the Birth Kontrol Program to prevent and reduce early neonatal deaths. ABSTRAK Pendahuluan: Kematian neonatal dini menyumbangkan sekitar 2/3 kematian anak. Tujuan: untuk melihat pengaruh penggunaan alat kontrasepsi dengan kematian neonatal dini. Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian case kontrol yang dilakukan di Puskesmas Sarmi pada tanggal 1 Juni – 31 November 2020 dengan sampel kasus adalah ibu yang mengalami kejadian neonatal dini sejumlah 34 orang dan sampel kontrol adalah ibu yang tidak mengalami kejadian neonatal dini sejumlah 166 orang dengan perbandingan 1: 5. Penelitian ini menggunakan data rekam medik tahun 2017-2019 Puskesmas Sarmi dengan analisis logistic regression model faktor risiko yang diolah menggunakan STATA 14. Hasil: Hasil penelitian ini menunjukkan adanya pengaruh penggunaan alat kontrasepsi terhadap kematian neonatal dini setelah di kontrol oleh variabel konfoding berupa usia kehamilan, jarak kehamilan, LILA, Kadar Hb, dan suku (p value 0,0001 dengan nilai OR sebesar 11,4 (95% CI= 4,5 – 29,5). Optimalisasi peran pendampingan kader dalam upaya meningkatkan partisipasi PUS dan WUS pada Program KB untuk mencegah dan mengurangi kematian neonatal dini.